Controlling the coassembly of highly amphiphilic block copolymers with a hydrolytic sol by solvent exchange1. Issue 29 (27th April 2015) - Guldin, Stefan; Stefik, Morgan; Sai, Hiroaki; Wiesner, Ulrich; Steiner, Ullrich
<x xml:space="preserve">Abstract</x> Block copolymer co-assembly of TiO2 is facilitated by the introduction of a redissolution step in an azeotrope solvent mixture, allowing the formation of self-assembled cylindrical, lamellar and hexagonal ceramic morphologies.